Https://www.fungiofpakistan.com: a continuously updated online database of fungi in Pakistan. (29th December 2021) - Raza, Mubashar; Cai, Lei; Abbasi, Muhammad Waseem; Tariq, Marium; Wijayawardene, Nalin N
Abstract: The website fungiofpakistan.com is a collection of all the available data about macro- as well as micro-fungi collected from Pakistan. This website comprises reported fungal species with isolation source or host record, locality and updated classification. The data on this website is based on old literature (library data, personal data of specific authors or books that were not easily accessible to public) and recent publications. This website is an important potential platform for researchers, government officials, industries and other users. Users can provide their inputs related to missing taxa, new genera, the new record and new data. They also have the opportunity to express their opinions on valid names, invalid names and illegitimate names, with notes published in the 'Notes' section of webpage provided following review and editing by curators and fungal taxonomists. This website plays a significant contribution to our knowledge of the rich fungal diversity of Pakistan. However, much more sustained and detailed research is needed to fully evaluate fungal diversity in Pakistan. Undoubtedly, that many more fungi will be discovered and added in the future. Database URL: https://fungiofpakistan.com/